2018
DOI: 10.15421/331813
|View full text |Cite
|
Sign up to set email alerts
|

Application of “PolySwitch” fuses for the limitation of current overloads in photovoltaic systems of solar arrays

Abstract: The results of experimental study of the transformation of the light current-voltage and volt-watt characteristics for the parallel connections of photovoltaic modules when using “PolySwitch” polymer resettable fuses are given. The conditions for selecting such fuses which allow their correctly triggering and minimize the current overload are formulated and experimentally verified. It is established that if resettable fuses are connected in series to the circuits of all photovoltaic modules, which are connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…sunny or cloudy day, time of year, etc.). Note: The points are the experiment (Ivanchenko et al, 2018), the solid line is the approximation…”
Section: Mmms 163mentioning
confidence: 99%
See 3 more Smart Citations
“…sunny or cloudy day, time of year, etc.). Note: The points are the experiment (Ivanchenko et al, 2018), the solid line is the approximation…”
Section: Mmms 163mentioning
confidence: 99%
“…The simplified circuit of PV array with protection against the indicated short circuits is shown in Figure 1 (Ivanchenko et al , 2018; Lyashkov et al , 2018; Tonkoshkur et al , 2019). The PV module was used as the PV component that was to be protected.…”
Section: Model Of Photovoltaic Array With Current Limitermentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, as one of the new areas of application of posistor elements based on the nanocomposites under consideration, they are used to solve the problems of constructing systems for protecting components of photovoltaic systems of solar cells from electrical overloads [11,12]. The general scheme and conditions for the use of resettable fuses to limit the current in parallel connections of photovoltaic modules by connecting a separate PPTC fuse in series with each module are justified [13]. It is shown that the series connection of self-healing PolySwitch fuses in photovoltaic modules when connected in parallel allows them to prevent contingencies of the complete loss of the electrical energy generated by this unit, which occurs when a short circuit in one of its modules.…”
Section: Introductionmentioning
confidence: 99%